Een nieuwe kijk op het stadhuis. - Manderyck, Madeleine (Antwerpen : Kathleen Overmeer, 2016)
Huet, Jan ; Nicolas, Joep ; Tuerlinckx, Jean-Pierre ; Staes, Georges ; Caen, Joost ; Van Riet, Jan ; Calders, Armand ; Bierwerts, Willem ; Tordoir, Narcisse ; Berckmans, Warner
450 jaar stadhuis Antwerpen, Inhuldiging glasraam, 26.02.2016
Schenking Flanders DC
boek